Lower Extremity Free Tissue Transfer in the Setting of Thrombophilia: Analysis of Perioperative Anticoagulation Protocols and Predictors of Flap Failure - DeFazio, Michael V.; Economides, James M.; Anghel, Ersilia L.; Tefera, Eshetu A.; Evans, Karen K. (Journal of Reconstructive Microsurgery, 2019)
Background No consensus exists regarding the optimal strategy for perioperative thromboprophylaxis in high-risk microsurgical populations. We present our experience with lower extremity free tissue transfer (FTT) in thrombophilic patients and compare outcomes between non-stratified and risk-stratified anticoagulation protocols.Methods Between January 2013 and December 2017, 57 patients with documented thrombophilia underwent FTT for non-traumatic, lower extremity reconstruction by a single surgeon. Patients were divided into two cohorts based on the introduction of a novel, risk-stratified algorithm for perioperative anticoagulation in July 2015. Demographic data, chemoprophylaxis profiles, flap outcomes, and complications were retrospectively compared across time periods.Results Fifty-seven free flaps were performed in hypercoagulable patients treated with non-stratified (n = 27) or risk-stratified (n = 30) thromboprophylaxis. Patients in the risk-stratified cohort received intravenous heparin more often than non-stratified controls (73 vs. 15%, p < 0.001). Lower rates of total (3 vs. 19%, p = 0.06) and partial (10 vs. 37%, p = 0.025) flap loss were observed among risk-stratified patients, paralleling a significant reduction in the prevalence of postoperative thrombotic events (1.2 vs. 12.3%, p = 0.004). While therapeutic versus low-dose heparin infusion was associated with improved flap survival following intraoperative microvascular compromise (86 vs. 25%, p = 0.04), salvage rates in the setting of postoperative thrombosis remained 0%, regardless of protocol. On multivariate analysis, recipient-vessel calcification (odds ratio [OR]: 16.7, p = 0.02) and anastomotic revision (OR, 3.3; p = 0.04) were independently associated with total flap failure.Conclusion Selective therapeutic anticoagulation may improve microsurgical outcomes in high-risk patients with thrombophilia. Our findings highlight the importance of meticulous technique and recipient-vessel selection as critical determinants of flap success in this population.
Keywords: anticoagulation; free tissue transfer; hypercoagulability; microsurgery; thrombophilia